A study on the consumer behaviour towards online shopping / Mohd Adnan Abdullah - Abdullah, Mohd Adnan (2014)
Consumer behaviours is the study of individuals, groups, or organizations and the processes they use to select, secure, and dispose of products, services, experiences, or ideas to satisfy needs and the impacts that these processes have on the consumer and society. The main goal of the paper is to obtain quantitative evidence describing the actuality of internet shopping in the case of the Papar District in order to explain the development of internet shopping and its impact on consumer behaviour. Online shopping made many impact in consumer's behaviour toward shopping activities. For that, my focus on this research is focusing on how do human behaviour gives impact on shopping activities in the internet. The research also to differentiate the service quality over the price which may impact people behaviour in online shopping. The privacy protection and kind of shipping and delivering the product also play a role to convince buyer especially in Papar's community. The 120 respondents have given some questionnaire and I have transferred the data to determine their behaviour in online shopping by scaled them into 5 scales. I will also discuss the people demographic data which may also gives impact on online shopping behaviour. For the conclusion, I will determine which factor has most influencing consumers' attitude and satisfaction towards online shopping especially for the people in Papar.